2022
DOI: 10.1002/vetr.1977
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long‐term management of hypoadrenocorticism on the quality of life of affected dogs and their owners

Abstract: Background The treatment of canine adrenal insufficiency consists of hormone substitution and requires high owner compliance and intense human–dog interaction. This might affect the quality of life (QoL) of owners and their pets. The aim of the study was to evaluate the impact of hypoadrenocorticism and its treatment on the QoL of dogs and their owners. Methods Owners completed a web‐based survey that contained items concerning signalment, owner QoL, dog QoL and long‐term therapy. Results Three hundred and twe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 29 publications
2
9
0
1
Order By: Relevance
“…A total of 322 owners of dogs with hypoadrenocorticism completed the survey, of which 255 were German-speaking and 67 were English-speaking. 11 Unlike some older reports, 3,8 dogs of both sexes were almost equally represented in the study cohort, but signalment and clinical signs were otherwise consistent with previous reports. 1,3,8 Although most owners indicated that their dog's disease did not affect their own quality of life, they reported multiple potential sources of quality of life impairment.…”
Section: What You Need To Knowsupporting
confidence: 84%
See 4 more Smart Citations
“…A total of 322 owners of dogs with hypoadrenocorticism completed the survey, of which 255 were German-speaking and 67 were English-speaking. 11 Unlike some older reports, 3,8 dogs of both sexes were almost equally represented in the study cohort, but signalment and clinical signs were otherwise consistent with previous reports. 1,3,8 Although most owners indicated that their dog's disease did not affect their own quality of life, they reported multiple potential sources of quality of life impairment.…”
Section: What You Need To Knowsupporting
confidence: 84%
“…To help address this knowledge gap, a study by Hupfeld and colleagues, summarised on p 417 of this issue of Vet Record, used an anonymous online survey to gather information regarding the effect of long-term management of hypoadrenocorticism on the quality of life of affected dogs and their owners. 11 Data collected included the affected dogs' signalment, clinical signs, time to diagnosis and details of the therapy administered and its adjustments. In addition, quality of life tools previously validated for diabetes mellitus 12 and hyperadrenocorticism 13 were used to assess the quality of life of both the owners and their dogs.…”
Section: What You Need To Knowmentioning
confidence: 99%
See 3 more Smart Citations